Neonatal Foot Length as Surrogate Marker for Prematurity: A Hospital Based Cross-Sectional Study in Central India - Kapoor, Anju; Soni, Triloki Nath (Journal of Nepal Paediatric Society, 2020)
Introduction: Neonatal mortality is higher in premature babies, more so when identification and intervention is delayed. This study was aimed to find out the effectiveness of foot length measurement, a simple and inexpensive method, for identifying premature babies at birth. Methods: This cross sectional study was conducted on 514 hospital born neonates. Their foot length, birth weight, length and head circumference were measured and compared with gestational age assessed by new Ballard score. Results: Amongst 514 newborns, 71.6% were term and 28.4% were preterm. Mean foot length in term and pre-term babies were 7.30 cm (SD + 0.39) and 6.81 cm (SD + 0.52) respectively (p value < 0.0001). Pearson's correlation coefficient between gestational age as assessed by new Ballard score and foot length, birth weight, length and head circumference all showed significant positive correlation in the decreasing order [maximum with foot length (r = 0.802)]. Linear regression analysis for gestational age with foot length also had highest coefficient of determination R2 = 0.760 (P < 0.001). Foot length with cut-off < 6.83 cm has higher AUC (Area Under Curve) and is a good marker for predicting prematurity with a sensitivity of 94.57%, and a specificity of 41.99%. Conclusions: Foot length measurement can be a good surrogate marker to predict prematurity as significant correlation is seen between it and gestational age assessed by new Ballard score.